Assessment of prognostic criteria in acute pancreatitis: Su utilización en la Unidad de Cuidados Intensivos del Hospital Pasteur - Misa, Ricardo; Jalda, Laura; Quiroga, Carlos; Bentancourt, Solveig (Cirugía del Uruguay, 2003)
Object: Revision of prognostic indexes in acute pancreatitis, its usefulness in predicting, the patient's inal outcome and possible onset of complications